Periacetabular Osteotomy as a Salvage Procedure: Early Outcomes in Patients Treated for Iatrogenic Hip Instability. (4th November 2020) - Brusalis, Christopher M.; Peck, Jeffrey; Wilkin, Geoffrey P.; Robustelli, Stacy; Buly, Robert L.; Nawabi, Danyal H.; Ranawat, Anil S.; Kelly, Bryan T.; Sink, Ernest L.
Abstract : Background: A periacetabular osteotomy (PAO) can reduce pain and improve quality of life in patients with hip dysplasia. While its utility for patients without traditional radiographic parameters for hip dysplasia has not been previously established, the PAO may help treat patients with hip instability that does not improve following single or multiple hip arthroscopic procedures, or when such procedures lead to hip instability. Methods: A single-surgeon registry of patients at a single institution was queried to identify patients with a lateral center-edge angle (LCEA) of ≥24° and a Tönnis angle of <10° who underwent PAO because of hip pain and/or instability that failed treatment with hip arthroscopy. Descriptive summary statistics were reported on patient demographics, mean change in LCEA, and patient-reported outcome measures, including the modified Harris hip score (mHHS) and the International Hip Outcome Tool-33 (iHOT-33), at a minimum of 6 months of follow-up. Results: Among 25 patients (mean age, 27.3 ± 6.9 years; 100% women), the mean LCEA increased from 27.2° (range, 24° to 37°) preoperatively to 39.0° ± 5.1° postoperatively (net increase, 11.8° ± 4.5°). Overall, the mean improvement in the mHHS was 11.5 ± 16.9 (preoperative, 59.4 ± 11.6; postoperative, 70.9 ± 20.6) and the mean improvement in the iHOT-33 was 23.8 ± 23.6 (preoperative, 32.2 ± 17.2; postoperative, 56.0 ± 30.0). Eighteen patients (72%) achieved a minimal clinically important improvement in mHHS (mean improvement, 17.4 ± 12.9) and iHOT-33 (mean improvement, 32.4 ± 19.1) scores. In comparison with 7 patients who did not show improvement, the 18 patients who showed improvement had significantly greater mean baseline patient-reported outcome scores. Conclusions: To our knowledge, these findings provide the first report on outcomes of PAO in patients with hip pain following arthroscopy who do not meet the traditional criteria for acetabular dysplasia. Early benefits in clinical outcomes suggest a novel surgical indication for PAO as a potential salvage option for selected patients; however, longer-term studies are needed. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.